EKSISTENSI PROKEM DI TENGAH MODERNISASI BAHASA GENERASI MILENIAL - Afrizal Mufti; Dita Pramestiani; Anggi Kusuma Maharani (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
The use and development of slang or slang is increasingly rapid along with the development of technology and advances in information media. Youth plays a major role in the distribution and development of slang as their true identity in socializing. This research is included in a qualitative descriptive study using the literature review method obtained from previous research journals in the research object of slang or slang. The purpose of this research is to analyze and thesis the phenomenon of the findings of slang, which is the result of this analysis, which is then able to provide a new knowledge base for research that will be carried out regarding the development of current slanguage. The research data is then analyzed using the PRISMA technique based on a collection of studies that have been carried out. The results of the analysis show that slogan is closely related to the identity of adolescents in social life. Several journal studies explain that the use of slang is influenced by several factors, one of which is environmental factors.Keywords:Â Existence; Prokeme; Millennial Generation